Sistem Perbaikan Faktor Daya Otomatis Berbasis Microcontroller Pada Beban Listrik Kapal - Hafid Arrafi; Sri Mulyanto; Novrico Susanto; Edi Kurniawan (Jurnal Kendali Teknik dan Sains, 2024)
Inductive loads on ships are loads that cause the power factor value to move away from 1.00, especially if the addition of this type of load exceeds the standard and the load is installed unbalanced, it can worsen the power factor value. A low power factor value results in soaring current values and reactive power, which often results in cable insulation burning and reduced efficiency. The aim of this research is to create a tool that can automatically correct low power factor values using a Capacitor Bank, PZEM-004T sensor and ESP32 controller at certain inductive loads and can monitor and record electrical load parameter data from various areas on the ship online and offline. This research uses a trial and error method. Based on the test results, this tool can automatically improve the power factor value of inductive loads in the form of TL lamps and electro motors to above 0.90 and the working current value of TL lamps can be reduced from 0.30-0.31 A to 0.17-0.18 A. Electro motors experience a decrease in current from 0.74-0.76 A to 0.66-0.68 A. This tool is also equipped with a system for monitoring and recording load parameter data using Google Spreadsheet when an internet connection is available. If an internet connection is not available, the recording will be transferred using Micro-SD.